Provincializing dialogue: post-secular governance networks and the brokerage of religious diversity in a North German town - Emmerich, Arndt (Interreligious encounters in Europe, 2023)
This chapter investigates the emergence of a post-secular governance network that focuses on migrant integration and the management of religious diversity in a small town in Northern Germany. Dominated by a Catholic minority leader in a majority Protestant region, the empirical analysis illustrates how a local cross-party, civil society, media and faith network, which has influenced the public discourse on interreligious relations, refugees and Islam for over ten years, operates and is perceived by supporters and opponents. Special consideration is given to the emerging academic discussion on religious diversity in rural areas and small towns in Germany, which, compared to research on major urban centres, assumes a different modality regarding the strength of networks, the role of traditional actors and the interplay between secular and religious factors. In doing so, the chapter engages with the notion of the ‘broker’ within political anthropology and scholarship on networks within organizational sociology, to inquire whether a provincial location with tight-knit bonds, regular and informal face-to-face interactions among local actors and mutual oversight through meta-governance produces more robust post-secular networks compared with large metropolitan centres.
Gesehen am 24.04.2023